Prayer in the Gospels : a theological exegesis of the ideal pray-er - Nygaard, Mathias (Leiden ; Boston : Brill, 2012)
In Prayer in the Gospels Mathias Nygaard offers a text-centred reading of the prayer materials of the Gospels. His approach provides for exegesis and theology in a single discussion.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 630
Keywords: Bible. -- Criticism, interpretation, etc; Bible; Prayer -- Biblical teaching; Prayer -- Biblical teaching; RELIGION -- Biblical Studies -- Jesus, the Gospels & Acts; RELIGION -- Biblical Studies -- New Testament; Prayer -- Biblical teaching; Electronic books; Criticism, interpretation, etc